Association of tumor volumetry with postoperative outcomes for cervical paraganglioma - Hoffmann-Wieker, Carola Marie; Gomes dos Santos Ferreira Rebelo, Artur Luis; Moll, Martin; Ronellenfitsch, Ulrich; Rengier, Fabian; Erhart, Philipp; Böckler, Dittmar; Ukkat, Jörg (Diagnostics, 2023)
Objectives: To analyze the association of tumor volume with outcome after surgery for cervical paraganglioma. Materials and Methods: This retrospective study included consecutive patients undergoing surgery for cervical paraganglioma from 2009-2020. Outcomes were 30-day morbidity, mortality, cranial nerve injury, and stroke. Preoperative CT/MRI was used for tumor volumetry. An association between the volume and the outcomes was explored in univariate and multivariable analyses. A receiver operating characteristic (ROC) curve was plotted, and the area under the curve (AUC) was calculated. The study was conducted and reported according to the STROBE statement. Results: Volumetry was successful in 37/47 (78.8%) of included patients. A 30-day morbidity occurred in 13/47 (27.6%) patients with no mortality. Fifteen cranial nerve lesions occurred in eleven patients. The mean tumor volume was 6.92 cm3 in patients without and 15.89 cm3 in patients with complications (p = 0.035) and 7.64 cm3 in patients without and 16.28 cm3 in patients with cranial nerve injury (p = 0.05). Neither the volume nor Shamblin grade was significantly associated with complications on multivariable analysis. The AUC was 0.691, indicating a poor to fair performance of volumetry in predicting postoperative complications. Conclusions: Surgery for cervical paraganglioma bears a relevant morbidity with a particular risk of cranial nerve lesions. Tumor volume is associated with morbidity, and MRI/CT volumetry can be used for risk stratification.